A new-curvature cellular automata model of austenite grain growth. (26th July 2019) - Li, Zhiqiang; Wang, Junsheng; Huang, Houbing
Abstract: A new-curvature three dimensional cellular automata model for grain coarsening is proposed. The model takes account of the effects of grain size on the local-curvature. The simulation results are analyzed from four aspects: grain growth kinetics, grain size distribution, dynamics of single grain, and topological properties. The grain growth kinetics of the present model is proved to agree well with the theoretical model of normal grain growth. The absolute values of average grain size are compared to the experimental results of a low alloy steel. The simulated grain size distribution can be satisfactorily described by the Werbull's formula. The simulation results of single grain growth kinetics matches well with the Hillert's theoretical model, and the topological properties are similar to Ding's simulation results.